The Effect Of M-B-C (Mind-Body-Counseling) Nursing Care Module On Cooping Strategies, Clinical Symptoms And Fetal Well-Being In Preeclampsia Mothers - Yenny Puspitasari; Arina Chusnatayaini (Journal of Health Science Community, 2023)
Preeclampsia is the most common complication, with an increasing incidence in the world, and is associated with maternal morbidity and mortality, which is around 2-8% of pregnancies. Mind-Body-Counseling (M-B-C) nursing care emphasizes the physical and psychological care that is needed in the management of preeclampsia patients.Objective: To explain the effect of Mind-Body-Counseling (M-B-C) nursing care on coping strategies, clinical symptoms, and fetal well-being in preeclampsia mothers. The research was conducted in two stages, the first stage (module building) and the second stage (quantitative analysis). Phase I of the research was carried out with literature review, qualitative research, and expert review to produce the Mind-Body-Counseling Module which was carried out in a period of approximately two months at RSUD dr. Soedomo Trenggalek. Phase II of the study was an experiment with the division of case and control groups with a total of 60 respondents who were mothers with preeclampsia at RSUD dr. Soetomo Surabaya. Mind-Body-Counseling (M-B-C) nursing care is provided with three assessments, namely coping strategies, clinical symptoms, and fetal well-being. The assessment used a questionnaire and was analyzed using descriptive analysis and the Wilcoxon test. The Mind-Body-Counseling (MBC) nursing care module consists of mind interventions to identify problems and stress responses, counseling interventions so that clients understand pregnancy with preeclampsia, and body interventions to reduce clinical symptoms. The results of the Phase II study showed a significant difference in coping strategy scores (p=0.000), systolic blood pressure (p=0.001), diastolic blood pressure (=0.018), urine protein (p=0.000), and fetal well-being (p=0.000) between control and intervention groups. After the intervention, it was concluded that there was a significant effect between Mind-Body-Counseling (MBC) nursing care on improving coping strategies, decreasing clinical symptoms, and increasing fetal well-being in preeclampsia mothers